Role of CRP in Lower Respiratory Tract Infections - Kaur, Jaskaranjot; Narang, Gursharan Singh; Arora, Sunita (Journal of Nepal Paediatric Society, 2013)
Introduction: Better diagnostic tests that establish the cause of LRTIs can reduce irrational antibiotic use. CRP is an acute phase protein that increases on inflammatory triggers can solve the purpose. The study aimed at role of CRP in distinguishing between bacterial and viral etiology. Materials and Methods: Fifty patients, aged 2 months to 5 years, with complaints of fever, cough and respiratory distress were included. Along with all other basic investigations like CBC, PBF, ESR, CRP Quantitative was also by Nycocard CRP Single Test for in vitro rapid determination. Results: In LRTI of probable bacterial aetiology mean CRP was 61.72 ±36.665 mg/l which was significantly higher than those with probable viral aetiology with mean CRP of 5.24 ±1.4 mg/l. The cut off level of CRP is taken as 9 mg/l with sensitivity of 100% and specificity of 96 %. Conclusion: CRP levels are both sensitive and specific for differentiating between viral and bacterial LRTI, thus reducing the overuse of antibiotics in clinical practice. DOI: http://dx.doi.org/10.3126/jnps.v33i2.8106 J Nepal Paediatr Soc. 2013; 33(2):117-120